THE INFLUENCE OF COMPETENCE ON EMPLOYEE PERFORMANCE AT THE AMANDRAYA DISTRICT OFFICE: PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT AMANDRAYA - Lasniroha Laia, Lusia (UPMI Proceeding Series, 2024)
The study aims to determine the influence of competence on employee performance at the Amandraya District Office, South Nias Regency. Competence is viewed as the ability of employees to apply knowledge, skills, and attitudes in the work context to achieve effective results. This study applies quantitative methods with a population of 17 employees. Data analysis was conducted through hypothesis testing using multiple linear regression. The results show that competence significantly influences employee performance both simultaneously and partially. The F-test indicates that the regression model is suitable for use, while the T-test reveals that the competence variable has a significant effect on employee performance. The coefficient of determination value of 52.3% shows that competence can significantly explain variations in employee performance.